Tubular Mechanism for the Spontaneous Hypercalciuria in Laboratory Rat - Lau, Kai; Eby, Bonnie K. (The Journal of Clinical Investigation, 1982)
Recently it has been observed that Ca excretion in laboratory rats does not follow a Gaussian distribution, with ∼10% of them excreting Ca at a rate of 2 SD above the group mean. This phenomenon has been described as spontaneous hypercalciuria (SH). Our studies were designed to define its mechanism. 48 Wistar rats were subjected to metabolic studies to identify SH, prospectively defined as Ca excretion 2 SD above the group mean during 7 d of dietary Ca deprivation (≤0.03% by analysis), in the absence of hypercalcemia, PO4 depletion, or exaggerated natriuresis. Progenies from SH rats were found to have significantly higher urine Ca/creatinine (micrograms per milligram) (male = 38 vs. 23, P < 0.05; female = 79 vs. 60, P < 0.005) with 7/20 males and 9/26 females having values 2 SD above the means of normal. After a 12-h fast and during 10% volume expansion with saline, clearance and micropuncture studies were performed on three groups of acutely parathyroidectomized female rats; (a) normocalciuric (N) progenies from the normal, (b) normocalciuric (NC) progenies from SH, and (c) hypercalciuric (HC) progenies from SH rats. Among these groups, there was no significant difference in body weights, glomerular filtration rate, plasma ultrafiltrable Ca (4.5, 4.6 vs. 4.7 mg/100 g), PO4, and the fractional excretion (FE) of Na or FEPO4. FE Ca was significantly higher in HC rats (13.9%) than N (10.1%) and NC (10.7%). Segmental reabsorption of fluid and Na was comparable among the three groups. Fractional delivery (FD) of Ca was, however, significantly increased in the late proximal tubule of HC rats (62 vs. 49 and 46%, P < 0.05). The increased FDCa was no longer apparent in early or late distal tubule (6.9 vs. 6.9 and 7.6%, P = NS). Although FECa exceeded late distal FDCa in all three groups, the increment was significantly greater in HC rats (7.02%) than both N (3.4, P < 0.05) and NC rats (3.05, P < 0.02). The effects of chlorothiazide (27.5 mg/kg/d, i.p. × 7 d) were evaluated in the female offsprings of the SH rats. Before chlorothiazide, average urine Ca/creatinine (253 vs. 77.2) and cyclic AMP (26.6 vs. 13.4 μmol/mg creatinine, P < 0.001) on days 7 and 8 of the Ca-deprived diet were higher than the normal. On days 6 and 7 of chlorothiazide, average cyclic AMP (cAMP) excretion fell to normal range (11.7 vs. 12.7 μmol/mg creatinine) as Ca excretion was reduced to normal (62 vs. 59.4 μg Ca/mg creatinine). We conclude: (a) SH, as defined in this study, is an inheritable biochemical marker and renal in origin. (b) The hypercalciuria is independent of parathyroid hormone, changes in plasma Ca and tubular handling of Na. (c) As studied in the PTX and volume expanded conditions of our experiments, decreased Ca reabsorption in superficial proximal convoluted tubule is demonstrable, but the hypercalciuria is probably mediated by diminished Ca transport by the deep nephron. The unlikely possibility of increased secretion by the terminal nephron, however, remains to be excluded. (d) In normal rats, there is internephron heterogeneity in regard to Ca transport during saline loading.